Conceptualizing more inclusive elections: violence against women in elections and gendered electoral violence. (3rd March 2020) - Schneider, Paige; Carroll, David
ABSTRACT: Violence against women in politics and throughout the election cycle has been documented as an impediment to the free and equal political participation of women, and to the conduct of inclusive elections. Academic research and practitioner assessments have raised the profile of this global problem, and draw attention to key challenges in theory development, the operationalization of concepts, and the creation of shared measures for data collection. This article seeks to contribute to the scholarship by positing a theoretical framework that situates violence against women in elections (VAWE) at the intersection of gender-based violence and political violence. We examine the role of gender in relationship to targets, perpetrators, motives, and forms of electoral violence to demonstrate the importance of studying violence motivated by gender discrimination alongside more conventional motives of electoral violence. The analysis is informed by examples drawn from field research in Uganda.